Overhead Power Line Tension Estimation Method Using Accelerometers - Sang-Hyun Kim; Kwan-Ho Chun (Energies)
Overhead power lines are important components of power grids, and the status of transmission line equipment directly affects the safe and reliable operation of power grids. In order to guarantee the reliable operation of lines and efficient usage of the power grid, the tension of overhead power is an important parameter to be measured. The tension of power lines can be calculated from the modal frequency, but the measured acceleration data obtained from the accelerometer is severely contaminated with noises. In this paper, a multiscale-based peak detection (M-AMPD) algorithm is used to find possible modal frequencies in the power spectral density of acceleration data. To obtain a reliable noise-free signal, median absolute deviations with baseline correction (MAD-BS) algorithm are applied. An accurate estimation of modal frequencies used for tension estimation is obtained by iteration of the MAD-BS algorithm and reduction in frequency range technique. The iterative range reduction technique improves the accuracy of the estimated tension of overhead power lines. An accurate estimation of overhead power line tension can contribute to improving the reliability and efficiency of the power grid. The proposed algorithm is implemented in MATLAB R2020a and verified by comparison with measured data by a tensiometer.